2021
DOI: 10.5812/gct.118755
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Microrna-195 Increased Significantly in Patients with Methamphetamine Abuse Disorder

Abstract: Background: Addiction is one of the most important social and health problems in the world. Development of rapid and inexpensive diagnostic methods for identification of patients with addiction to methamphetamine is still a very important challenge. Recently, microRNAs (miRNAs) have been introduced as an accurate and reliable biomarker for diagnosis of human disorders. Objectives: In the present study, the expression of miRNA-186 and miRNA-195 was investigated in blood of patients with methamphetamine abuse di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Moreover, difference of clinical characteristics between case and healthy controls was investigated by Chi-square and independent sample t-test. The difference with a p < 0.05 was considered statistically significant [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, difference of clinical characteristics between case and healthy controls was investigated by Chi-square and independent sample t-test. The difference with a p < 0.05 was considered statistically significant [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that dysregulated various miR-NAs are involved in neurogenesis, neuronal function, and other neurobiological processes, such as synaptic plasticity, which are associated with drug addiction [12][13][14]. Moreover, brain-enriched miRNAs, such as miR-222 and miR-212, have been reported to be involved in development of addiction by directly manipulating dendritic spine morphogenesis, synaptic remodeling, and the rewarding properties of drugs, drug-seeking behavior, and self-administration rates of alcohol [13,15]. Identification of specific miRNAs involved in the addiction process is important to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation